The Cyclically Resolvable Steiner Triple Systems of Order 57 - Svetlana Topalova; Stela Zhelezova (Mathematics)
A resolution of a Steiner triple system of order v (STS(v)) is point-cyclic if it has an automorphism permuting the points in one cycle. An STS(v) is cyclically resolvable if it has at least one point-cyclic resolution. Cyclically resolvable STS(v)s have important applications in Coding Theory. They have been classified up to <semantics>v=45</semantics> and before the present work <semantics>v=57</semantics> was the first open case. There are 2,353,310 cyclic STS(57)s. We establish that 155,966 of them are cyclically resolvable yielding 3,638,984 point-cyclic resolutions which we classify with respect to their automorphism groups and to the availability of some configurations.